First to the front : the untold story of Dickey Chapelle, trailblazing female war correspondent - Rinehart, Lorissa (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2023)
"From the beginning of World War II through the early days of Vietnam, groundbreaking female photojournalist and war correspondent Dickey Chapelle chased dangerous assignments her male colleagues wouldn't touch, pioneering a radical style of reporting that focused on the humanity of the oppressed. She documented conditions across Eastern Europe in the wake of the second world war. She marched down the Ho Chi Minh Trail with the South Vietnamese Army and across the Sierra Maestra Mountains with Castro. She was the first reporter accredited with the Algerian Revolutionary Army and survived torture in a communist Hungarian prison. She dove out of planes, faked her own kidnapping, and endured the mockery of male associates, before ultimately dying on assignment in Vietnam with the Marines in 1965, the first American female journalist killed while covering combat. Chapelle overcame discrimination and abuse, both on the battlefield and at home, with much of her work ultimately buried from the public eye-until now. In First to the Front, Lorissa Rinehart uncovers the incredible life and unparalleled achievements of this true pioneer, and the mark she would make on history"--